Beban Kerja Subyektif dan Obyektif Tenaga Farmasi Rawat Jalan di Rumah Sakit - Vreza Budi Setiawan; Ratna Dwi Wulandari (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
In 2014 patient visits to pharmacy services increased 75% from the previous year. Man power in the pharmacy unit was not comparable with the number of pharmacy service.The availability of human resources isinadequate when being compared to the number of outpatient pharmacy visits, therefore it influenced the respon time up to 43,91% for non paten drugs which as not in accordance with the standart services minimum pharmacy services. This data indicate that there was overload capacity on man power in outpatient pharmacy unit. The purpose of this study was to show wordload category on man power in outpatient pharmacy unit, particularly to pharmacists and assistants pharmacists. This was quantitative descriptive study. There were 26 samples consisting of 1 pharmacist, 16 asisstants pharmacists in depo 1 and 9 asisstants pharmacists in depo 5 outpatient pharmacy unit. Data collected by observation for 2 week in working hours. Result of the study was pharmacicts and assitants pharmacists in depo 1 had subjective and objective workload in overload category while depo 5 inmoderate category.Keywords: subjective and objective workload, pharmacicts and assitants pharmacists, work sampling